Sanduq: A microfinance innovation in Jabal Al-Hoss, Syria - Hans Dieter Seibel; Omar Imady (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2003)
Jabal al-Hoss is one of the poorest areas in Syria where UNDP has supported the establishment of self-reliant local financial institutions, sanduq (sg.) lit. savings box: a novel concept in centralized banking system. The sanadiq (pl.) are self-managed and autonomous in their decision-making, which has included the adoption of financial practices consistent with local values. The start-up is self-financed through member share capital, from which small loans are given for up to three months. Whenever initial financial intermediation is satisfactory, UNDP provides an additional capital injection, thereby increasing outreach, loan sizes and loan periods. Between September 2000 and December 2002, 22 sanadiq were established, comprising 4,691 members, with shareholder equity of US 130,000. UNDP contributed 370,000 in equity. The repayment rate as of 31 December 2002 was 99.7%. Return on average equity was 17%, almost half of which (46%) was paid to shareholders, the balance (54%) retained as capital. Loans permit farmers to bypass trader-moneylenders and sell their produce at a higher price; laborers turn into farmers; and micro-entrepreneurs use quick-turnover repeat loans for new investments and rapid business growth. Special attention is given to women who constitute 41% of the membership, most of them illiterate. They opted for integrated sanadiq, in which female members participate in management committees. They find access to loans easy, as sanadiq do not require physical collateral. Loans are used by younger and older women to do business of their own, eg, fattening sheep, raising cows, opening small shops and renting land to plant cash crops. The additional income is used for business growth and family support. It is not rare that women – many with large families – are the better entrepreneurs, focusing on high-yielding activities outside traditional agriculture. In 2002 first steps were taken towards the establishment of a network which will provide apex services and initiate the dialog on a legal framework; and of a central fund (Sanduq Markazi) supervised by the Central Auditing Agency. During phase II, 2003-2007, with support from the Japanese Government and UNDP, the focus is now on the expansion and legal consolidation of the network of sanadiq. There are also plans for extending such networks throughout Syria as a strategy for rural development, poverty alleviation and employment generation. (For further details and a pictorial view see www.undp-hoss.com)
Keywords: 330; Mikrofinanzierung; Informeller Finanzsektor; Syrien